PERBANDINGAN BIAYA DAN DURASI PELAKSANAAN PEKERJAAN BEKISTING MULTIPLEKS DAN BATAKO PADA PEKERJAAN PILE CAP PROYEK DOUBLE – DOUBLE TRACK STASIUN MANGGARAI - Hastanto SM; Gilang Yulianto (Sekolah Tinggi Teknik - PLN, 2017)
Selection of a method is very important in the implementation of a construction project, because the right method can give maximum results, especially in terms of cost and time. For example the method of pile cap formwork where there are various methods such as conventional formwork, multiplex formwork, bekako batako, fiberglass formwork and knock down formwork. In this study, comparative cost and duration of multiplex formwork and brick to accumulate Manggarai station work station, by searching the area and volume of both methods. To calculate the cost of using HSP Regulation of the Minister of Public Works No.11 / PRT / M / 2013 by using unit price of materials and wages in DKI Jakarta, while for the period is calculated based on the coefficient of the two methods (OH). The results of this study obtained multiplex formwork cost for six times the use of Rp. 1.494.595.028 while the cost of building a brick is Rp. 2.298.269.374,84 more efficient 34.97% of the cost of making multiplex formwork and for the duration of the implementation of the formwork multiplex 46.69% faster than the brick formwork seen on the pylon P4 is 4.03 days and formwork brick 7.56 day.